Restoration and Representation of Yoruba Culture in the Lion and the Jewel: A Stylistic Study - Paul Nepapleh Nkamta; Dekera Gerald Atim (Journal of Mother-Tongue Biblical Hermeneutics and Theology)
This study examines the stylistic restoration and representation of Yoruba culture in Wole Soyinka’s The Lion and the Jewel, focusing on how linguistic choices serve as vehicles for cultural preservation and dramatic expression. Through detailed analysis of the play’s language, the study demonstrates how Soyinka creates a sophisticated dramatic idiom that successfully bridges traditional Yoruba cultural expression and modern theatrical conventions. The study identifies and analyses several key linguistic phenomena, including Yorubanised English, character-specific linguistic patterns, ritual language, and gender-linked discourse. The analysis reveals how different characters’ linguistic choices reflect their positions in the cultural conflict between tradition and modernity, with a particular emphasis on Lakunle’s affected modernism, Baroka’s traditional authority, and female characters’ strategic manipulation of linguistic forms. The study demonstrates how Soyinka’s stylistic choices create a “cultural-linguistic palimpsest” where multiple layers of meaning and cultural reference coexist within single utterances. Gender relations are shown to be mediated through sophisticated linguistic strategies. The findings indicate that successful cultural representation in drama requires the use of new dramatic idioms, which accommodate both traditional and modern modes of expression, and maintain artistic coherence. This study contributes to understanding how dramatic language can serve as a vehicle for cultural preservation while creating compelling theatrical experiences, suggesting new approaches to analysing the intersection of language, culture, and dramatic form in postcolonial contexts.